Phantasie zum Presto agitato der Cis moll-Sonate von Beethoven - Lutz, A., engraver; Jericke, R. (artist):::Creator::::::::::::; Bodenmüller, Friedrich, 1804-1877 (artist):::Contributor:::::::::::: (Franz Hanfstaengl)
Allegorical image inspired by the last movement of Beethoven's "Moonlight" Sonata